2007
DOI: 10.1097/gme.0b013e318046eb4a
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms, menopause status, and country differences

Abstract: Similarities among core symptoms and differences in the expression of symptoms were found across sites. Both biological (menopause status) and cultural (country of residence) variables influence symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(65 citation statements)
references
References 35 publications
3
56
1
5
Order By: Relevance
“…W orldwide, hot flashes are among the most commonly reported symptoms among women transitioning through menopause, [1][2][3][4][5][6] and in certain populations, hot flashes affect up to 75% of women undergoing this transition. 1 Both the perimenopausal and postmenopausal stages of the transition are characterized by hot flashes, with perimenopause lasting 5-10 years 7,8 in some populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…W orldwide, hot flashes are among the most commonly reported symptoms among women transitioning through menopause, [1][2][3][4][5][6] and in certain populations, hot flashes affect up to 75% of women undergoing this transition. 1 Both the perimenopausal and postmenopausal stages of the transition are characterized by hot flashes, with perimenopause lasting 5-10 years 7,8 in some populations.…”
Section: Introductionmentioning
confidence: 99%
“…Ameliorating the effect of hot flashes on daily life is important because hot flashes are associated with a decrease in quality of life and are the most common reason for seeking medical intervention during the menopausal transition. 1,7,10 To date, few risk factors for hot flashes have been identified; those that have been identified include black race, [11][12][13] obesity, [13][14][15][16][17] cigarette smoking, 3,4,[12][13][14][15][16][17][18][19] and alcohol consumption. 13,16,20,21 The relationship between hot flashes and certain reproductive history variables, including age at menarche, age at first and last pregnancy, and parity, is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…The size of our cohort allowed us to analyze specifically women who experienced menopause during follow-up, resulting in a restriction of our population, but diminishing the potential for a recall bias without creating any selection bias, and concentrating our analysis on critical periods. Most previous studies focused on the prevalence of menopausal symptoms [2][3][4][5][6]8,9,12], which reflects both their onset and their duration in an indistinguishable manner. Moreover, previous studies on menopausal symptoms either included or excluded women on HRT [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…These may occur before or after the onset of menopause. Studies on the prevalence of menopausal symptoms during menopausal transition have reported that these were more likely to be experienced in late menopausal transition and in early postmenopause [2][3][4][5][6][7][8][9][10][11][12]. However, the main methodologic issues that limit inferences from epidemiologic studies of the menopausal transition are lack of longitudinal studies and short follow-up [5,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation